Cerebral astroblastoma-a rare and elusive case - Subhasish Panda; Rajesh Pattanaik; Savitri Bhagat; Nisa S.; Braja Beharis Panda; Bararuchi Dash (International Journal of Medical Research and Review, 2016)
Background: Astroblastoma is rare neuroglial intracranial tumor most commonly occurring in the first three decades of life.Case report: A 5 year old female child presented with intermittent headache, diplopia and recurrent seizures over a period of approximately 4 months. Her neurological examination revealed 6th nerve palsy and papilledema. Both CT and MRI revealed a well defined enhancing solid-cystic mass in the left fronto-parietal cerebral cortex with mass effect suggestive of primitive neuroectodermal tumor. She underwent gross total resection of the lesion through craniotomy. Histopathology along with immunohistochemistry was surprisingly suggestive of astroblastoma.Conclusion: Astroblastomas are very rare and often misdiagnosed.